Finance, inequality and inclusive education in Sub-Saharan Africa - Simplice Asongu; Joseph Nnanna; Paul N. Acha-Anyi (African Governance and Development Institute (AGDI), 2020)
This research complements the extant literature by establishing inequality critical masses that should not be exceeded in order for financial access to promote gender parity inclusive education in Sub-Saharan Africa. The focus is on 42 countries in the sub-region and the data is for the period 2004-2014. The estimation approach is the Generalized Method of Moments. When remittances are involved in the conditioning information set, the Palma ratio should not exceed 6.000 in order for financial access to promote gender parity inclusive "primary and secondary education" and the Atkinson index should not exceed 0.695 in order for financial access to promote inclusive tertiary education. However, when the internet is involved in the conditioning information set, it is established that in order for financial access to promote inclusive primary and secondary education, the: (i) Gini coefficient should not exceed 0.571; (ii) Atkinson index should not be above 0.750 and (iii) Palma ratio should be maintained below 8.000. Irrespective of variable in the conditioning information set, what is apparent is that inequality decreases the incidence of financial access on inclusive education. Hence, a common policy measure is to reduce inequality in order to promote inclusive education using the financial access mechanism. Policy implications are discussed in the light of Sustainable Development Goals.
Keywords: G20; I10; I32; O40; O55; 330; Africa; Finance; Gender; Inclusive development